Association between MethylenetetrahydrofolateReductase (MTHFR) GenePolymorphisms and breast cancer in sample of Iraqi women - Salman , Ehab D.; Al Bayyar , Ezeddin A.; Ibrahim, Reem K. (Iraqi Journal of Science, 2022)
Folate metabolism is fundamental and essential for DNA structure synthesis and repair. Change in genes that participate in folate metabolism can be linked with different types of malignant tumor, Therefore, this study was conducted to find out the association between methylenetetrahydrofolatereductaseMTHFR gene polymorphisms and risk of breast cancer in a sample of Iraqi patients. One Single Nucleotide Polymorphism ( SNP) including MTHFR C677T was calculated using a tetra primer ARMS PCR experiment assay. The results explained that (MTHFR C677T) consists of three genotype (CC, CT, TT), The CC genotype was the most frequent in patients and control group ( 40.00%) and(60.00%) ,respectively, while the lowest frequency was for TT genotype(26.25%) in patients group .This study also revealed that the higher frequency 56.88 % for allele C and 43.12 % for T allele in patients group . On the other hand the Odd Ratio ( O.R.) for CC, CT , TT genotypes were 1.073, 0.862 and 1.148 respectively, and the genotypes TT show a highest O.R.